Rwanda : Education Resilience Case Report - World Bank (Washington, DC, 2014)
Rwanda was selected as one of the major case studies to inform the development of Education Resilience Approaches (ERA) tools and background materials because of its remarkable recovery economically, socially, and politically from the impact of the terrible 1994 Genocide. This recovery has been particularly marked in the education sector which has undergone a series of reforms designed to promote peaceful social transformation.